Improvement of treatment adherence with growth hormone by easypod™ device: experience of an Italian centre - Maria Cristina Maggio; Beatrice Vergara; Paolo Porcelli; Giovanni Corsello (BMC, 2018)
Abstract Background One of the most important vulnerabilities falling the efficacy of recombinant human growth hormone (r-hGH) treatment is low adherence especially in young patients. This study was planned to describe the correlation between r-hGH treatment efficacy and adherence in real-life setting using easypod™. Methods Forty patients younger than 18 years, affected by a clinical condition in which r-hGH is available and treated with r-hGH easypod™, were enrolled in a retrospective, observational, real-world data, monocentric trial. The study design provided the retrospective collection of records collected by a questionnaire proposed to the patients and their parents and compared with registered data by the new generation electronic device r-hGH easypod™. Number of injections and doses were collected and used to assess the percentage of administered GH doses to measure treatment adherence. The r-hGH treatment efficacy was evaluated comparing standard deviation score for height (SDS) between baseline and follow-up visit, according to clinical practice. Results The mean treatment adherence was 92.20% and it was inversely related to patients' age (R = − 0.358, p = 0.023), and significantly higher in the sub-group of patients with age between 10 and 13 years. Treatment adherence showed an inverse correlation with the years of therapy (R = − 0.453, p = 0.003) and with the number of r-hGH administrations (R = − 0.392, p = 0.012). However, the height increase did not reach a significant correlation with treatment adherence (R = − 0.067, p = 0.683). Conclusions Children and adolescent patients with GH deficiency due to different clinical conditions show high adherence to r-hGH treatment tested by easypod™. Easypod™ could be used as an important device to control patients' adherence in daily treatment for chronic diseases with expensive drugs.